Learning Strategies for the Segara Strait Dance for Teenagers at the Asmarandana Balinese Dance Studio in Bandung City - Desya Noviansya Suherman; Devi Supriyatna (Raja Zulkarnain Education Foundation, 2025)
nanti dalam bahasa Inggris